In vitro sensitivity of Gammarus pulex to controlled exposure to Copper and Aluminum Sulfates - Cedeño Moreira, Angel Virgilio (2024)
Aquatic ecosystems, essential for water purification, climate regulation and biodiversity conservation, face increasingly worrying threats due to the release of contaminants, including copper sulfate and aluminum sulfate. These compounds, exert serious adverse effects on the health of aquatic organisms and the integrity of their biological niches. This study focuses on Gammarus pulex, a highly sensitive indicator of pollution in aquatic habitats. To address this research, a rigorous methodology was implemented that ranged from the isolation and identification of G. pulex individuals to their acclimatization and subsequent controlled exposure to copper and aluminum sulfate. Comprehensive evaluation of the effects of this exposure included in detailed morphometric and population analyses. The results revealed that all studied concentrations of these contaminants caused significant reductions in the growth of G. pulex populations. Noting, worryingly, that treatment with Al2(SO4)5 during an exposure period of 48 hours and at a concentration of 40 ppm resulted in 100% mortality. Together, these findings underscore the urgent need to address copper sulfate and aluminum sulfate pollution in aquatic ecosystems, recognizing the vulnerability of key species such as G. pulex. Preserving the health of these populations and conserving the integrity of aquatic ecosystems is essential to ensure the proper functioning and sustainability of these valuable habitats.